Les coopératives de montagne en Slovaquie - Michel Lompech (Revue de Géographie Alpine)
One third of Slovakia is covered by mountain range where cooperatives are the main agricultural actors. These collective farms were created within the frame of the former administered economy and have survived its break up. The specific temporality of the collectivization in mountain and the structure of local communities are important factors in the stages of change. The paper aims at estimating the effects of the mountain context in the restructuring of the cooperatives and gives a typology of the current forms of cooperatives in mountain areas.